2014
DOI: 10.1002/jpln.201200445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar application of organic acids on alleviation of aluminum toxicity in alfalfa

Abstract: Organic acids (OA) may affect plant resistance to aluminum (Al) toxicity in acidic soils. However, limited information is available on the effects of different organic acids on Al resistance in alfalfa. We investigated the effects of foliar application of organic acids (succinic acid, citric acid, malic acid, and oxalic acid) to alfalfa (Medicago sativa L.) under Al stress. Seedlings were grown in pH 4.5 nutrient solution containing Al at 0 or 100 μM, and were sprayed with water or 100 μM of oxalic acid, malic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…The gene expression changes induced by Al would affect the synthesis of succinyl-CoA and in turn influenced OA synthesis in the TCA (tricarboxylic acid) cycle. An et al [10] investigated that Al could affect the synthesis of OAs by influencing the TCA cycle, and the foliar application of succinic acid could increase the accumulation of organic acids (including oxalic acid, malic acid, citric acid, and succinic acid) and alleviate Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene expression changes induced by Al would affect the synthesis of succinyl-CoA and in turn influenced OA synthesis in the TCA (tricarboxylic acid) cycle. An et al [10] investigated that Al could affect the synthesis of OAs by influencing the TCA cycle, and the foliar application of succinic acid could increase the accumulation of organic acids (including oxalic acid, malic acid, citric acid, and succinic acid) and alleviate Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports have suggested that organic acids (OAs) play an important role in the mechanism by which plants tolerate Al stress [10]. Plants also have other mechanisms to cope with Al stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that mineral absorption could be affected by elevated exudation of organic acids in response to foliar organic acids (Jaafari and Hadavi, 2012). However this is confirmed recently by An et al (2014), and the intervention of these exudates in mineral absorption in the soil is well known (Bais et al, 2006;Arcand and Schneider, 2006;Marschener, 1998).…”
Section: Essential Oil Parametersmentioning
confidence: 77%
“…Jafari and Hadavi (2012), suggested an increase in mineral absorption by elevated exudation of organic acids in response to foliar organic acids as part of mechanism responsible for improved growth parameters. This was confirmed recently by An et al (2014), and the mediation of these exudates in mineral absorption in the soil medium is well known (Marschener, 1998;Bais et al, 2006;Arcand and Schneider, 2006). In addition, the exudated organic acids are the main carbon source for rhizobacteria (Ohwaki and Sugahara, 1997).…”
Section: Introductionmentioning
confidence: 74%
“…Organic acids are involved in a broad range of physiological processes of plant growth and development (An et al, 2014), and are also considered to alleviate biotic stresses (Jafari and Hadavi, 2012). Endogenous organic acids are the source of both carbon skeleton and energy for cells, and are used in the respiratory cycle and other biochemical pathways.…”
Section: Introductionmentioning
confidence: 99%